1990
DOI: 10.1136/bjo.74.5.283
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of local and systemic acyclovir in the management of herpetic disciform keratitis.

Abstract: Forty-three patients with active herpetic disciform keratitis were entered into an open study to compare the efficacy of oral acyclovir (400 mg) with acyclovir ophthalmic ointment (3%) to inhibit viral replication during treatment with 0-05% prednisolone eye drops. All patients, regardless of the mode of therapy, were treated five times a day until they were healed. The mean time to heal in the oral group was 25 9 days and in the topical group was 25 3 days. Resolution of lacrimation was significantly faster i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 9 publications
2
15
1
Order By: Relevance
“…These lesions can be distinguished from the neurotrophic keratopathy that can develop in patients with recurrent herpes infectious epithelial keratitis by virtue of the swollen epithelial cells and scalloped borders at the margins of herpetic lesions. Because herpetic epithelial lesions are caused by viral cytopathic effect, the lesions can be self-limiting (i.e., controlled by innate and/or adaptive immunity), but heal more rapidly when treated with antiviral drugs, such as trifluorothymidine (TFT) and acyclovir (ACV) (Pavan-Langston and Foster, 1977; Porter et al, 1990). …”
Section: Herpetic Infectionmentioning
confidence: 99%
“…These lesions can be distinguished from the neurotrophic keratopathy that can develop in patients with recurrent herpes infectious epithelial keratitis by virtue of the swollen epithelial cells and scalloped borders at the margins of herpetic lesions. Because herpetic epithelial lesions are caused by viral cytopathic effect, the lesions can be self-limiting (i.e., controlled by innate and/or adaptive immunity), but heal more rapidly when treated with antiviral drugs, such as trifluorothymidine (TFT) and acyclovir (ACV) (Pavan-Langston and Foster, 1977; Porter et al, 1990). …”
Section: Herpetic Infectionmentioning
confidence: 99%
“…Collum et al [1] reported that the total healing times were a mean of 5 and 5.6 days both in oral and topical ACV-treated patients with herpetic dendritic keratitis [4] . However, Porter et al [4] found signifi cantly longer healing times in patients with disciform keratitis treated with either oral or topical ACV (mean 25.9 and 25.3 days, respectively). Since our study included both patients with epithelial and stromal herpetic keratitis it was logical to expect such a healing time.…”
Section: Discussionmentioning
confidence: 99%
“…Oral ACV has widely been used in the treatment of herpes simplex keratitis and was reported to have a similar effi cacy to topical ACV ointment therapy [1,4] . Oral ACV has also been shown to be effective in the treatment of disciform herpetic keratitis [5] .…”
Section: Discussionmentioning
confidence: 99%
“…For endothelial HSK, there is not enough clinical trial evidence or guidelines to recommend an appropriate anti‐viral dosage. One clinical trial supported the use of an anti‐viral agent such as aciclovir 400 mg five times daily plus a topical corticosteroid five times daily, which we use as a guide in our study. To prevent episodes of HSK, aciclovir 400 mg twice daily for at least a year can reduce the rate of epithelial and stromal HSK episodes…”
Section: Introductionmentioning
confidence: 99%